Factors for increasing strength of composite materials based on fine high-calcium fly ash - Olga M. Sharonova; Leonid A. Solovyov; Alexander G. Anshits (Chimica Techno Acta)
Industrial high-calcium fly ashes obtained by burning Kansk-Achinsk coal at a thermal power plant and selected from different fields of electrostatic precipitators of an ash collecting plant were studied as the basis for composite binders (CB). The main factors influencing the properties of such CBs are the particle size, the concentration of superplasticizer at a water:binder (w/b) ratio of 0.25, and the proportion of HCFA in the mixture with cement. In particular, for cementless CBs at w/b 0.4, it was found that a change in the particle size d90 from 30 μm to 10 μm leads to an increase in compressive strength by more than 2 times – from 5.5–14 MPa to 11–36 MPa, accordingly, with a curing age of 3–300 days. The 0.12% additive of Melflux 5581F superplasticizer at w/b 0.25 increases the compressive strength – up to 14–32 MPa and up to 24–78 MPa, accordingly. The HCFA-cement blends were investigated in the range of 60–90% HCFA and the maximum compressive strength 77 MPa at 28 days of hardening was found at 80% HCFA. On the basis of 80% HCFA blend with the 0.3% addition of Melflux 5581F and 5% silica fume, the specimens of ultra-high strength (108 MPa at 28 days of hardening) were obtained.